A proposed order-level classification in Oligochaeta (Annelida, Clitellata) - Schmelz, Rüdiger M.; Erséus, Christer; Martin, Patrick; Haaren, Ton Van; Timm, Tarmo (Zootaxa, 2021)
The purpose of our contribution is to propose a robust and practical order-level classification of the families of Oligochaeta, that is, non-leech Clitellata. The order level is mandatory in Linnaean rank-based classification and is also required in many internet-based biodiversity databases. However, it has received little attention in oligochaete systematics, and the few available order-level classifications of Oligochaeta no longer represent phylogenetic relationships adequately. Our proposal is based on corroborated molecular phylogenetic evidence and takes as benchmarks class level for Clitellata, subclass level for Oligochaeta and Hirudinea, and order level for Crassiclitellata, the monophylum that includes most of the earthworm taxa. As a result, eleven orders are proposed: Alluroidida Timm & Martin, 2015; Capilloventrida Timm, n. ordo; Crassiclitellata Jamieson, 1988; Enchytraeida Kasprzak, 1984; Haplotaxida Brinkhurst & Jamieson, 1971; Lumbriculida Brinkhurst & Jamieson, 1971; Moniligastrida Brinkhurst & Jamieson, 1971; Narapida Timm, n. ordo; Parvidrilida Timm, n. ordo; Randiellida Jamieson, 1988; Tubificida Jamieson, 1978. This order-level classification is robust and easily adaptable to future insights into phylogenetic relationships.